Biomechanical Evaluation of Different Orthodontic Archwire Materials and Their Effect on Tooth Movement Efficiency - Abhay Kumar Jain; Khumanthem Savana; Shresthaa Singh; Brajendu; Shovan Roy; Parul Priya (Journal of Pharmacy and Bioallied Sciences)
Background: Orthodontic treatment relies on the efficient movement of teeth, which is influenced by the material properties of archwires. Materials and Methods: This study involved 60 patients undergoing orthodontic treatment, randomly assigned to three groups, each using a different type of archwire material: stainless steel (SS), nickel–titanium (NiTi), and beta-titanium (TMA). The evaluation was conducted over 6 months, measuring tooth movement efficiency, force delivery, and patient discomfort. Tooth movement was recorded monthly using digital models, and force delivery was assessed using a universal testing machine. Patient discomfort was evaluated through a standardized questionnaire. Results: The NiTi archwire group showed the highest tooth movement efficiency, with an average movement of 1.2 mm/month, followed by the SS group with 1.0 mm/month, and the TMA group with 0.9 mm/month. Force delivery was most consistent with the NiTi wires, maintaining an average force of 200 g over the treatment period. Patient discomfort was significantly lower in the NiTi group (mean score of 3.2) compared to the SS (mean score of 4.5) and TMA groups (mean score of 4.1). Conclusion: Nickel–titanium archwires demonstrated superior tooth movement efficiency and consistent force delivery with reduced patient discomfort compared to stainless steel and beta-titanium archwires.